Rectified Pulley Suture for the synthesis of tensioned skin wounds - Marcos Fernando Tudino; João Pedro Gouveia Gonçalves; Valéria do Amaral; Igor Roszkowski (Revista Brasileira de Cirurgia Plástica, 2024)
Introduction: The synthesis of tensioned skin wounds is an area that has been the subject of studies for the development of suturing techniques that are capable of performing the primary closure of these wounds with tension relief, ensuring adequate healing, and avoiding complications such as dehiscence, edema, bleeding, and infection. Method: This research was a pilot study, being the first presentation of the Rectified Pulley Suture technique for the synthesis of tensioned skin wounds through prospective, double-blind monitoring of a series of cases of 8 patients randomly admitted to the surgical center of a high-complexity hospital in a medium-sized city. Results: Rectified Pulley Suture is a versatile technique suitable for dealing with tensioned skin wounds, since intraoperatively it was able to close, by first intention, lesions measuring up to 6.5 centimeters and in different tensioned regions without the need for the use of more extensive techniques. complex, such as flaps, grafts, Z-plasty, and secondary intention closure. Furthermore, post-operatively, there was a reduction in POSAS scores, indicating a satisfactory healing process for both observers and the patient. It is also essential to mention that the most feared outcome in the follow-up of patients with tension wounds undergoing primary closure - dehiscence - was completely avoided. Conclusion: The technique is simple, reliable, safe, and reproducible, with a short learning curve, so the Rectified Pulley Suture can be considered a new tool to be integrated into the surgical arsenal.